Entropy generation and heat transfer in Time-Fractional mixed convection of nanofluids in Darcy-Forchheimer porous channel - Zafar Hayat Khan; Oluwole Daniel Makinde; Alexander Trounev; Waqar Ahmed Khan; Rashid Ahmad (Engineering Science and Technology, an International Journal)
This study investigates the role of time-fractional derivatives in the entropy analysis of mixed convection in a reacting nanofluid within a vertical permeable channel saturated with a Darcy-Forchheimer porous medium. This is crucial for enhancing heat and mass transfer, incorporating memory effects, and addressing delayed responses in various engineering applications. Key phenomena such as thermophoresis, porous medium permeability, buoyancy forces, chemical reactions, viscous dissipation, Brownian motion, and velocity slip are considered. The study presents an advanced computational methodology that integrates the Euler wavelets collocation method with an implicit difference scheme to discretize the system of time-fractional partial differential equations. This advanced numerical framework is thoroughly validated, ensuring high accuracy in capturing the complex interactions between fluids and solids. The study reveals that a 20% increase in the Eckert number leads to a 15% rise in entropy generation, signifying greater energy dissipation within the system. Likewise, higher Reynolds numbers contribute to increased entropy generation, emphasizing the flow’s dissipative nature. On the other hand, a 10% increase in pressure gradient and Forchheimer parameters results in a 12% reduction in entropy generation, demonstrating their ability to control the system’s irreversibility. These findings pave the way for more optimized and energy-efficient designs in engineering systems involving porous media.